Comparison between short-term upper body power and double-pole peak VO2 in cross-country skiers - Staib, J. L.; Im, J.; Rundell, K. W. (Medicine & Science in Sports & Exercise, 1999)
Top US cross-country ski racers (N = 23) completed an upper body power test and a double-poling test to exhaustion.